Current Issues in Oral Health: Introduction to the Special Issue - Nejat Düzgüneş (Oral, 2025)
This Special Issue of Oral exemplifies a broad range of problems in oral health and the delivery of oral healthcare, ranging from treating the fear of dental care to the detection of oral lesions by artificial intelligence [...]